The economics of financial markets and institutions : from first principles - Sussman, Oren (Oxford University Press, 2024)
This manuscript is based on introductory lectures on financial economics that I delivered to masters students in the Faculty of Law at the University of Oxford. We approach financial economics as an application of general economic theory to both financial markets and financial institutions. Accordingly, we present both the general economic theory and its financial applications.